The Influence of Incentive Program on Employee Job Satisfaction: The Role of Organizational Commitment as a Mediation Variable in PT. Starion Wooin - Saginata Adirama, Dyo; Bimanti Esthi, Raniasari (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to evaluate the impact of incentive programs on employee job satisfaction, with organizational commitment as a mediating variable at PT. Starion Wooin, a manufacturing company producing electronic and automotive components. A quantitative approach was used through a survey method. Data were collected via questionnaires from 122 respondents in the Quality Control department and analyzed using PLS-SEM with SmartPLS 4.0. The results show that incentive programs significantly affect job satisfaction (β = 0.375; t = 3.664; p < 0.001). Organizational commitment mediates this relationship (β = 0.294; t = 4.123; p < 0.001). R² for job satisfaction is 0.584, indicating moderate explanatory power. These findings suggest that companies should not only focus on financial incentives but also consider non-financial aspects such as recognition, career development opportunities, and overall employee well-being. Building a strong organizational culture is also essential to strengthen commitment and maximize the effectiveness of incentive programs. Thus, PT. Starion Wooin and other companies in the manufacturing sector are encouraged to design more comprehensive incentive policies to improve employee satisfaction and loyalty, ultimately supporting business sustainability and competitiveness.